2012
DOI: 10.1158/1078-0432.ccr-11-2395
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epstein-Barr Virus–Encoded Proteins in Extranodal NK/T-cell Lymphoma, Nasal Type (ENKL): Differences in Biologic and Clinical Behaviors of LMP1-Positive and -Negative ENKL

Abstract: Purpose: Extranodal NK/T-cell lymphoma, nasal type (ENKL) is closely associated with Epstein-Barr virus (EBV). To elucidate its pathogenetic role, we examined the expression profiles of EBV-encoded proteins, especially focusing on latent membrane protein 1 (LMP1).Experimental Design: Immunohistochemistry was carried out using clinical samples from ENKL cases, which were diagnosed between 1996 and 2010 at our institution. We statistically assessed the correlation between LMP1 positivity and the clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Use of the IPI for predicting prognosis and selecting therapeutic options remains controversial in ENKL, [14,15,16] and has not been predictive of prognosis [28,29]. Unfavorable prognostic factors have been reported, including advanced-stage disease (stage III/IV), invasion of bone or skin, EBV DNA levels, and low absolute lymphocyte counts [20,21,30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the IPI for predicting prognosis and selecting therapeutic options remains controversial in ENKL, [14,15,16] and has not been predictive of prognosis [28,29]. Unfavorable prognostic factors have been reported, including advanced-stage disease (stage III/IV), invasion of bone or skin, EBV DNA levels, and low absolute lymphocyte counts [20,21,30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…5 patients (including 2 primary nasal ENKL, 1 primary lymph node ENKL, 1 primary liver ENKL, 1 primary intestines ENKL) had more than 6.1 × 10 7 copies/ml EBV DNA, with an OS of 60%. It has been demonstrated that the copy number of free EBV DNA is correlated with a negative prognosis [20,31,32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intestine was one of the most common extranasal sites of ENKTL-N involvement, with a relatively high frequency of metastasis and dismal follow-up outcomes. Although the pathogenesis remains unclear, EBV infection was thought to be a triggering risk factor of the tumor genesis [8,29] . Although DLBCL was also the most common histological subtype in the intestinal tract in other studies, the second most common subtype varies from region to region.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] EBV-encoded latent membrane protein expression correlated with the phosphorylation of RelA and Akt possibly had a favorable impact on clinical outcome in patients with ENKTLs. 20,40 Among pathology parameters, an adverse prognosis was correlated with a high Ki-67 labeling index and EBV DNA load but not with cellular morphology or the expression of CD56. 30,31,41 Pongpruttipan et al 8 suggested that patients with a T-cell ENKTL in the upper airway tended to have better survival although this did not reach statistical significance.…”
Section: Modern Pathology (2016) 29 430-443mentioning
confidence: 99%